Immune Checkpoint Inhibition as Single Therapy for Synchronous Cancers Exhibiting Hypermutation: An IRRDC Study. (2nd March 2022) - Henderson, Jacob J.; Das, Anirban; Morgenstern, Daniel A.; Sudhaman, Sumedha; Bianchi, Vanessa; Chung, Jill; Negm, Logine; Edwards, Melissa; Kram, David E.; Osborn, Michael; Hawkins, Cynthia; Bouffet, Eric; et al.
Abstract :